BUILD COMPUTER NETWORK USING TCP / IP VERSION 6 - Yudi Irawan Chandra (Majalah SIKOMTEK, 2004)
This paper will explain about IP version 6 and how pengalokasiannya. This time to request anIP address that has been done through agencies appointed by the IANA (Internet AssignedNumbers Authority) which is determined on a regional basis, such as APNIC (Asia PacificNetwork Information Center), which handles special requests IP addresses for the AsiaPacific region, including areas served by APNIC is Indonesian. Similar organizations thathandle regions of North America, South America, the Caribbean, and Sub-Saharan Africa isARIN, whereas in Europe, the Middle East, and parts of Africa is the RIPE-NCC.